The study of blockages effect at leading edge on rectangular cavity in subsonic flow using particle image velocimetry (PIV) - Annuar, Ahsan Nur Mubarak; Mohd Rafie, Azmin Shakrine; Hameed Sultan, Mohamed Thariq (Trans Tech Publications, 2013)
In this present paper, laminar cavity flow is analysed at Re = 5.12 x 104 based on cavity length. The experiments were conducted in an open subsonic wind tunnel using Particle Image Velocimetry (PIV). A rectangular cavity with constant depth of 4 cm with length-to-depth ratio of 4 was used. Several types of blockage had been located at the leading edge of cavity and each experiment was performed by acquiring 700 image pairs to filter out the velocity vectors. The results are given in terms of mean velocity profile accordingly and compared thoroughly by dividing cavity into 4 sections. The result had been shown in mean velocity profile in u and v velocity component.